2017
DOI: 10.1108/jerer-06-2016-0023
|View full text |Cite
|
Sign up to set email alerts
|

Is energy performance too taxing?

Abstract: Type footer information here Type header information here Structured Abstract [Mandatory]-Please structure in sections as shown in the author guidelines Purpose: Buildings contribute significantly to CO2 production. They are also subject to considerable taxation based on value. Analysis shows that whilst similar attributes contribute to both value and CO2 production, there is generally a loose relationship between the two. If we wish to use taxation to affect policy change (drive energy efficiency behaviour), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 28 publications
1
2
0
Order By: Relevance
“…Accordingly, behavioural factors seem to certainly play a key role, and this appears to be more prominent in rural areas in relation to PV uptake, and arguably driven by small-scale one-off development such as “green jewellery” self-builds – through integrated renewable energy design and desirability for “going green” and/or the identification of “cost savings” achievable through the adoption of PV systems. Indeed, this finding, in accordance with Davis et al (2017), which also revealed an urban-rural divide in energy efficiency in the housing stock, pointing towards a potentially more receptive population regarding environmental consciousness and awareness driven by peer effects networking within the agriculture community. This is further substantiated when considering the nature of the existing housing stock in rural versus urban locales.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Accordingly, behavioural factors seem to certainly play a key role, and this appears to be more prominent in rural areas in relation to PV uptake, and arguably driven by small-scale one-off development such as “green jewellery” self-builds – through integrated renewable energy design and desirability for “going green” and/or the identification of “cost savings” achievable through the adoption of PV systems. Indeed, this finding, in accordance with Davis et al (2017), which also revealed an urban-rural divide in energy efficiency in the housing stock, pointing towards a potentially more receptive population regarding environmental consciousness and awareness driven by peer effects networking within the agriculture community. This is further substantiated when considering the nature of the existing housing stock in rural versus urban locales.…”
Section: Discussionsupporting
confidence: 84%
“…Further, existing research into measuring the level of carbon emissions within the residential stock has also provided empirical evidence of the energy performance challenges. The study by Davis et al (2017) into the assessment of the level of CO 2 emissions of housing in NI revealed that most benefits can be gained by improving the performance of dwellings located in rural, as opposed to urban areas. More specifically, they identified that core urban areas appear to be the best or "greenest" in terms of the level of carbon dioxide per kilogram per annum (CO 2 Kgm 2 p.a.…”
Section: Introductionmentioning
confidence: 99%
“…Policy-wise, Davis et al (2017) uses the EPC scores to model the effects of a tax-based switch to energy efficiency and to understand the tax incidence effects of such a policy. Yuan and Choudhary (2020) uses EPC information together with domestic gas consumption and social factors to provide a locally tailored design of residential heating policies.…”
Section: Analyses Of Epcs In Researchmentioning
confidence: 99%